Pattern size dependence of Si1-xGex epitaxial growth for high mobility device applications - Lee, Jooyoung; Kim, Hyungjun; Bao, Mingqiang; Wang, Kang L. (ELSEVIER SCIENCE SA, 2006)
Pattern size dependence of etch pit dislocations (EPDs), strain relaxation and Hall mobility has been investigated in Si0.62Ge0.38 alloy layers grown on a patterned Si template with different sizes of trench openings isolated by oxide. The results show that the EPD density is significantly reduced from 24000 to 6400 cm(-2) as the pattern size decreases from 500 x 500 to 10 x 10 mu m(2). The Hall mobility is also greatly enhanced as the pattern size decreases, particularly at low temperature. These results represent that the dislocation and surface roughness are dominant limiting factors of the mobility in the SiGe epitaxial layers. The dislocations are effectively reduced and the smoother surface roughness is achieved using the pattern guided epitaxy. The nano-scaled pattern guided epitaxial growth may provide a promising method for future high mobility and low dimensional device applications. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: MISFIT DISLOCATION DENSITY; SCATTERING; HETEROSTRUCTURES; MECHANISMS; REDUCTION; STRAIN